Influence of Different Soil Types on Dissolved Organic Matter Spectral Characteristics of Soil Leachate After Green Manure Tilling in Saline Soils - Chengjie Yin; Yuhao Wang; Xiaohui Ji; Wenjun Chi; Xiangjie Jiao; Yuejuan Yang; Xinwei Liu (Agronomy)
To investigate the changes in the composition and structure of the dissolved organic matter (DOM) of the lysate solutions of different types of soil after green manure tilling treatment, we set up two types of soil materials (fluvo-aquic soil; coastal saline soil) and three green manure tilling treatments (T1: CK—without green manure, T2: tilling Dongmu70 rye, and T3: tilling rapeseed green manure); then, the soil leachate was obtained with a soil column simulation test and its DOM spectral properties were determined. The rapeseed green manure leachate demonstrated a significantly higher humic macromolecule content and aromaticity compared to Dongmu70 rye leachate. Fluorescence Index (FI) values (1.5–2.2) suggest a mixed origin of dissolved organic matter (DOM) from both terrestrial and microbial-derived sources. All Humification Index (HIX) values remained below 1, indicating low humification levels and limited stabilization of DOM within the leachate system, and Biological Index (BIX) values exceeding 1 across all soil layers highlight the predominance of a recent biological metabolism in shaping DOM autochthonous origins. The SUVA260 values in Dongmu70 rye–moist soils and rapeseed green manure–coastal saline soil exhibited reductions of 0.020–2.573 L·(mg·m)−1 relative to pre-drenching levels. After tilling rapeseed green manure, the SUVA254 value of coastal saline soil at the 60–90 cm layer decreased by 1.941 L·(mg·m)−1. This study shows that differences in green manure and soil type affect DOM sources and composition, reducing DOM leaching, with coastal saline soil + rapeseed green manure and fluvo-aquic soil + Dongmu70 rye being the advantageous combinations. The study results provide theoretical guidance for applying green manure coupled with freshwater leaching technology in the context of saline and alkaline land with multiple soil types.